THE ROLE OF SELF EFFICACY IN IMPROVING INDIVIDUAL PERFORMANCE: A LITERATURE REVIEW - Mafrukhah, Inavatul; Eliyana, Anis; Rizki Sridadi, Ahmad (PT Naureen Digital Education, 2024)
This Systematic Literature Review explores in depth related to self efficacy variables which include antecedents, consequences, and research objects used ini self efficacy research. This Systematic Literature Review focuses on structured identification of self efficacy with a time span of the last ten years with restrictions on countries in Southeast Asia. This research method uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Based on the search, there are 30 relevant articles to be used as guidelines for preparing the Systematic Literature Review. The results showed that the antecedents of self efficacy were dominated by individual aspects, organizational aspects and technological aspects. Whilw the consequences of self efficacy are dominated by perceived usefulness, perceived ease to use, behavioral intention and performance. The object of research tends to examine the point of view of students and teachers (academics).